Occupational demands associated with rotator cuff disease surgery in the UK Biobank - Elizabeth L Yanik; Jay D Keener; Martin J Stevens; Karen E Walker-Bone; Ann Marie Dale; Yinjiao Ma; Graham A Colditz; Rick W Wright; Nancy L Saccone; Nitin B Jain; Bradley A Evanoff (Scandinavian Journal of Work, Environment & Health, 2023)

(untitled)
OBJECTIVES: Physically-demanding occupations may increase rotator cuff disease (RCD) risk and need for surgery. We linked a job-exposure matrix (JEM) to the UK Biobank cohort study to measure physical occupational exposures and estimate associations with RCD surgery. METHODS: Jobs and UK Standard Occupational Classification (SOC) codes were recorded during the UK Biobank verbal interview. Lifetime job histories were captured through a web-based survey. UK SOC codes were linked to a JEM based on the US O*NET database. O*NET-based scores [static strength, dynamic strength, general physical activities, handling/moving objects (range=1–7), time spent using hands, whole body vibration, and cramped/awkward positions (range=1–5)] were assigned to jobs. RCD surgeries were identified through linked national hospital inpatient records. Multivariable Cox regression was used to calculate hazard ratios (HR) as estimates of associations with RCD surgery. Among those with lifetime job histories, associations were estimated for duration of time with greatest exposure (top quartile of exposure). RESULTS: Of 277 808 people reporting jobs, 1997 (0.7%) had an inpatient RCD surgery. After adjusting for age, sex, race, education, area deprivation, and body mass index, all O*NET variables considered were associated with RCD surgery (HR per point increase range=1.10–1.45, all P<0.005). A total of 100 929 people reported lifetime job histories, in which greater exposures were significantly associated with RCD surgery after >10 years of work (eg, HR for 11–20 versus 0 years with static strength score ≥4 = 2.06, 95% confidence interval 1.39–3.04). CONCLUSIONS: Workplace physical demands are an important risk factor for RCD surgery, particularly for workers with more than a decade of exposure.